Do Live Weight, Body Condition Score, Back Muscle or Back-Fat Reserves Create the Suspicion of Goats Infected with Eimeria or Trichostrongylids? - Ptáček, Martin; Kyriánová, Iveta Angela; Nápravníková, Jana; Ducháček, Jaromír; Husák, Tomáš; Chay-Canul, Alfonso J; Zaragoza-Vera, Claudia; Cruz-Bacab, Luis; Vadlejch, Jaroslav (Animals, 2021)
Thirty goats of the breeds Czech Brown Shorthaired and Czech White Shorthaired and their crosses were randomly selected from a flock at a farm in the Czech Republic. All animals were monitored for one year at monthly intervals for their nutritional status (live weight, LW; body-condition score, BCS; depth of musculus longissimus thoracis et lumborum, MLTL; back-fat thickness, BT) and infection intensity with Eimeria sp. (EIM) and strongylid nematodes (STR). Regression-correlation analysis showed a possible interrelation of BCS with EIM infection. Analysis of muscle and fat reserves indicated that BT was better than MLTL in identifying EIM infection. Goat nutritional status was not significantly correlated with STR infection. A linear tendency (p = 0.092), however, was detected for the response of MLTL to STR infection. Results of this study indicated theoretical use of BCS for Eimeria identification and suggested some perspective of BCS for targeting animals infected by strongylid nematode. Validity of our results, however, was limited by number of observed animals managed under specific breeding conditions.
Keywords: strongylid nematodes; parasitic control; depth of musculus longissimus thoracis et lumborum